Letermovir prophylaxis is effective in preventing cytomegalovirus reactivation after allogeneic hematopoietic cell transplantation: single-center real-world data - Derigs, Patrick; Radujković, Aleksandar; Schubert, Maria-Luisa; Schnitzler, Paul; Schöning, Tilman; Müller-Tidow, Carsten; Hegenbart, Ute; Schönland, Stefan; Luft, Thomas; Dreger, Peter; Schmitt, Michael (Annals of hematology, 2021)
Morbidity and mortality after allogeneic hematopoietic cell transplantation (alloHCT) are still essentially affected by reactivation of cytomegalovirus (CMV). We evaluated 80 seropositive patients transplanted consecutively between March 2018 and March 2019 who received letermovir (LET) prophylaxis from engraftment until day +100 and retrospectively compared them with 80 patients without LET allografted between January 2017 and March 2018. The primary endpoint of this study was the cumulative incidence (CI) of clinically significant CMV infection (CS-CMVi) defined as CMV reactivation demanding preemptive treatment or CMV disease. With 14% CI of CS-CMVi at day +100 (11 events) was significantly lower in the LET cohort when compared to the control group (33 events, 41%; HR 0.29; p < 0.001). Whereas therapy with foscarnet could be completely avoided in the LET group, 7 out of 80 patients in the control cohort received foscarnet, resulting in 151 extra in-patient days for foscarnet administration (p = 0.002). One-year overall survival was 72% in the control arm vs 84% in the LET arm (HR 0.75 [95%CI 0.43-1.30]; p < 0.306). This study confirms efficacy and safety of LET for prophylaxis of CS-CMVi after alloHCT in a real-world setting, resulting in a significant patient benefit by reducing hospitalization needs and exposure to potentially toxic antiviral drugs for treatment of CMV reactivation.
Published: 03 December 2020
Gesehen am 12.08.2021